Spatial location and agglomeration economies in exports: Empirical evidence by technological intensities in Brazil - Antonio Carlos de Campos; Luis Lopes; Carlos Carreira (Journal of Applied Economics, 2023)
This study investigates spatial autocorrelation and the formation of spatial export clusters of Brazilian mesoregions based on technological intensity. It also analyzes how regional knowledge and agglomeration economies explain regional exports, using spatial econometric techniques. Brazilian exports exhibit a stronger spatial autocorrelation. Non-manufacturing sectors, which are less technology-intensive, exhibit lower spatial dependence than manufacturing sectors. The results also show an autocorrelation between exports and R&D expenditure, identifying the formation of clusters in the southeastern and southern regions. R&D expenditure fosters the growth of regional exports and the spatial lag effects of exports and R&D expenditure are significant in the high technology-intensive manufacturing sector.
Keywords: 330; Agglomeration economies; exports; R&D expenditure; spillovers